Analisis Technology Acceptance Model terhadap Penggunaan Canva Berbasis AI dalam Pemasaran Digital oleh Siswa SMK Jurusan Pemasaran di Kota Semarang - Juventius Wahyu Utama; Florentina Ajeng Tiya Pratiwi; Anoki Herdian Dito; Bonaventura Hendrawan Maranatha; Dian Prasetyo Widyaningtyas; Wulandari Wulandari (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
Data from 2024 shows that Canva has more than 170 million users, with Indonesia contributing 5.9% of the total global users. The Technology Acceptance Model (TAM) is used to analyze the acceptance of AI technology in Canva, especially in the context of vocational education. This study aims to examine the extent to which vocational high school students majoring in marketing accept and utilize AI technology in Canva to support academic assignments and marketing practices. This study also refers to previous studies that show that perceptions of usefulness and ease of use have a significant effect on user intention and satisfaction in utilizing AI-based technology. This study employs a mixed-methods approach, combining experiments with one-shot techniques with quantitative methods. The sample used in this study was 95 students from SMK Fransiskus, SMK Kristen Terang Bangsa, SMK Ignatius, and SMK Cut Nya'Dien Semarang majoring in marketing. The results of the study show that there is no direct influence between the variables of usefulness (perceived of usefulness) and perceived ease of use (ease of use) on the tendency to use (behavioural intention) of AI technology on Canva, but it will have a significant influence on the actualization of use (actual use) if mediated by the variable of tendency to use.